Brain oxygenation with a non‐vasoactive perfluorocarbon emulsion in a rat model of traumatic brain injury. (11th April 2018) - Abutarboush, Rania; Mullah, Saad H.; Saha, Biswajit K.; Haque, Ashraful; Walker, Peter B.; Aligbe, Chioma; Pappas, Georgina; Tran Ho, Lam Thuy Vi; Arnaud, Francoise G.; Auker, Charles R.; McCarron, Richard M.; Scultetus, Anke H.; et al.
Abstract: Objective: The aim of this study was to assess, in two experiments, the safety and efficacy of the PFC emulsion Oxycyte as an oxygen therapeutic for TBI to test the hypothesis that early administration of this oxygen‐carrying fluid post‐TBI would improve brain tissue oxygenation (Pbt O2 ). Methods: The first experiment assessed the effects of Oxycyte on cerebral vasoactivity in healthy, uninjured rats using intravital microscopy. The second experiment investigated the effect of Oxycyte on cerebral Pbt O2 using the PQM in TBI model. Animals in the Oxycyte group received a single injection of Oxycyte (6 mL/kg) shortly after TBI, while NON animals received no treatment. Results: Oxycyte did not cause vasoconstriction in small‐ (<50 μm) or medium‐ (50‐100 μm) sized pial arterioles nor did it cause a significant change in blood pressure. Treatment with Oxycyte while breathing 100% O2 did not improve Pbt O2 . However, in rats ventilated with ~40% O2, Pbt O2 improved to near pre‐TBI values within 105 minutes after Oxycyte injection. Conclusions: Although Oxycyte did not cause cerebral vasoconstriction, its use at the dose tested while breathing 100% O2 did not improve Pbt O2 following TBI. However, Oxycyte treatment while breathing a lower enriched oxygen concentration may improve Pbt O2 after TBI.